Analisis Keterbukaan Sikap Wihara Nam Hai Kwan Se Im Pu Sa Terhadap Agama dan Kepercayaan Lain - Satria Adhitama (Kamaya: Jurnal Ilmu Agama, 2023)
Indonesia is a pluralistic country with various religious entities and beliefs that live and develop in Indonesia. This plurality has the potential to cause conflict. Conflict can be avoided by the openness of religious institutions towards other religions or beliefs. One of the ways to show this is the openness of a house of worship towards other religions and beliefs. This research aims to dig deeper into the openness of the attitude of the Nam Ha Kwan Se Im Pu Sa Temple towards other religions and beliefs. Data was collected by deep interviews, observation, and documentation. The selection of informants or research subjects was carried out purposively. This temple has a very open attitude towards other religions and beliefs by making altars or pavilions for holy figures of other religions and beliefs. This temple not only honors Buddhist figures but also other figures such as Macopo from Taoism, Spiritual Bells from Confucianism, Our Lady from Catholicism, Lord Ganesha from Hinduism, Eyang Semar from Java, Eyang Prabu Siliwangi from Tatar Sunda, and Nyai Roro Kidul who is trusted by local residents as the sovereign of the South Sea. In addition to erecting altars and pavilions for holy figures of other religions and beliefs, this temple also organizes religious rituals adapted to local culture. Not only during cap go, the Kliwon Friday Night ritual is also carried out by this temple.